Gender Analysis of the Cambodian Labor Market - Gavalyugova, Dimitria; Cunningham, Wendy (World Bank, Washington, DC, 2020)
This paper has six sections. The authors begin with an overview of the gender-specific trends in labor force participation, industry employment shares, overall shifts in wage employment, and gender gaps in wages and educational attainment in Cambodia. The authors continue with an industry-specific look at wage employment trends, which confirms that, while there are a few emerging higher-skilled sectors such as financial services, the manufacturing sector (and the garment sector in particular) still dominates and continues to grow in importance for women’s wage work. The authors then shed light on the vertical occupational segregation patterns within industry and show that even if women are not underrepresented in manager positions in the dominant manufacturing (garment) sector, this type of positions represent less than one percent of all manufacturing jobs. In fact, at present the only sector providing prospects for career growth beyond low-skilled work is the services industry, where women are underrepresented as managers, but overrepresented as professionals and clerical workers. Moving on to wages, we test whether the gender wage gap and the factors contributing to it differ by industry. Occupational levels and education seem to play a role in explaining only a fraction of the wage gaps in construction and agriculture respectively, while the gender gap in trade remains completely unexplained by observable characteristics. What is of even greater interest is the fact that there is no gender wage gap in manufacturing, while the gap in services appears only after controlling for education and occupational level. Importantly, in all sectors other than manufacturing, women with identical characteristics and similar occupations still earn significantly less than men. The authors also explore the extent to which motherhood explains women’s labor force experiences. The presence of young children in the household do not seem to explain the gap in wages. Nevertheless, we show that they significantly increase the probability that a woman will transition to non-wage employment, likely due to the need to combine household duties, childcare and work. Inspired by literature in similar country contexts, authors then demonstrate that the sizeable expansion of job opportunities for women in the garment sector has likely had a disproportionately negative influence on Cambodian girls’ retention beyond primary schooling (compared to boys), thus limiting their employment and wage opportunities. Because of the continued role that non-wage employment plays in women’s occupational paths, authors finish the paper with an overview of the trends in the sector, with a focus on non-farm enterprises, which appear to be slowly taking over agriculture.